ASSESSING THE IMPACT OF HCV ON C- REACTIVE PROTEIN TO IMPROVE RISK IDENTIFICATION AND TREATMENT ENHANCEMENT IN PAKISTAN (The Research of Medical Science Review, 2025)
Background: Among the many systemic symptoms that are associated with hepatitis C infection, inflammation is one of the most prominent ones. There are a variety of viral and inflammatory disorders that have been associated to C-reactive protein (CRP), which is a sign of inflammation that is universally recognized. Objectives: The correlation between HCV and CRP levels, an indicator of systemic inflammation, was examined in this study. Methodology: The research employed a sample size of 772 individuals, consisting of 573 patients and 199 controls. CRP levels were measured in HCV- positive patients. Some additional parameters, including Liver function test, Complete blood count, and Renal function test, were computed in order to ascertain their correlations with the CRP level. Results: When compared to the control group, patients inflicted with HCV demonstrated a statistically significant elevation in CRP levels. This finding suggests that there is a correlation between HCV and an increased level of CRP. Conclusion: Gaining insight into the function of CRP in inflammation associated with HCV could potentially impact the management and surveillance of the disease.